2021
DOI: 10.1016/j.ijcha.2021.100823
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome treatment delay in low to middle-income countries: A systematic review

Abstract: Although morbidity and mortality rates are declining for acute coronary syndrome (ACS) in most high-income countries, it is rising at an alarming pace for low to middle income countries (LMICs). A major factor that is contributing to the poor clinical outcomes among LMICs is largely due to prehospital treatment delays. This systematic review was conducted to determine the mean length of time from symptom onset to treatment in LMICs and the sociodemographic, clinical and health system characteristics that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 50 publications
5
24
1
1
Order By: Relevance
“…Besides, patients with fewer SMuRFs were also accompanied with other poor risk profiles (more females, poorly educated, and admitted to county-level hospitals). Previous studies have reported that those unfavorable factors, as well as the existence of those individual components of SMuRFs, were associated with longer pre-hospital delay [ 26 – 28 ], which was consistent with our finding that patients with no SMuRF experienced significantly longer time from onset to FMC compared with their counterparts. Thus, this might also explain the clear differences in severity of illness at admission that patients with fewer SMuRFs presented with higher GRACE risk scores.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, patients with fewer SMuRFs were also accompanied with other poor risk profiles (more females, poorly educated, and admitted to county-level hospitals). Previous studies have reported that those unfavorable factors, as well as the existence of those individual components of SMuRFs, were associated with longer pre-hospital delay [ 26 – 28 ], which was consistent with our finding that patients with no SMuRF experienced significantly longer time from onset to FMC compared with their counterparts. Thus, this might also explain the clear differences in severity of illness at admission that patients with fewer SMuRFs presented with higher GRACE risk scores.…”
Section: Discussionsupporting
confidence: 93%
“…It is estimated that for every 1-minute delay to treatment, there is an 2% increase in mortality [41]. Use of EMS is an essential service that has been shown to reduce delay in ACS treatment in LMICs [42]. In the present study, the majority preferred for someone to drive them to the hospital rather than have EMS come to their home.…”
Section: Discussionmentioning
confidence: 79%
“…Most IHD deaths are from acute coronary syndromes (ACS), particularly in developing countries such as China [ 8 ]. Previous studies have identified numerous challenges in ACS treatment, including systematic delays and poor and unequal quality across different regions [ 9 13 ]. Time is critical for patients, and early diagnosis and treatment following clinical pathways are crucial to improving ACS care quality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%